Socio-Economic Impact of the Creation and Operation of Mega-Science Projects - N. Nurakhov, N.; S. Malyshev, A.; Kolesnikova, E.A.; Yu. Tsvetus, N. (International Journal of Criminology and Sociology, 2022)
Challenges of development facing society and states require efforts consolidation, in the research field in particular. Therefore, to organize international cooperation and to conduct basic and applied research, mega-science infrastructures are being created and implemented all over the world. Currently, research facilities of the mega-science class are being created in the Russian Federation. They play an important role in the development of science and the innovation process. The competitiveness of Russian science is a determining factor for ensuring the safety and technological independence of Russia. Therefore, the Federal program for the development of Synchrotron and Neutron research and research infrastructure for 2019-2027 was approved in March 2020. In the present article, the concept of the socio-economic impact of the operation of large-scale research infrastructure is revealed. The authors refer to the materials on the socio-economic impact analysis, which was based on the data on the Swedish neutron source (European Spallation Source). The article provides a generalized idea of the main indicators for assessing the potential of the research infrastructure as well as their application to characterize the research facilities in the Russian Federation. It is worth highlighting that each large research facility is unique and it is not possible to unify the analysis of the socio-economic impact. However, the obtained results can be used for a similar analysis of research infrastructures, based on the same physical principles and created to solve general scientific problems.